All roads lead home [videorecording (DVD)] - Fallon, Dennis; Delaney, Doug; Coyote, Peter; London, Jason; Cardone, Vivien, 1993-; Boyle, Peter, 1946-; Oswalt, Patton, 1969-; Branch, Vanessa, 1973-; Parke, Evan, 1968-; Bowlby, April, 1980- (Distributed by Anchor Bay Entertainment, 2009)
Belle, an animal-loving 12-year-old, becomes withdrawn after her mother's death in an automobile accident. Rebelling against her father, she is sent to live at the horse ranch of her gruff maternal grandfather. With the help of the animals, Belle's work on the farm transforms the entire family.